Roles of gut microbiota and metabolites in overweight and obesity of children - Zhang, Shengan; Dang, Yanqi (Frontiers in Endocrinology, 2022)
The prevalence of overweight and obesity in children and adolescents is an increasing public health problem. Pediatric overweight and obesity result from multiple factors, including genetic background, diet, and lifestyle. In addition, the gut microbiota and their metabolites play crucial roles in the progression of overweight and obesity. Therefore, we reviewed the roles of gut microbiota in overweight/obese children. The relationship between pediatric overweight/obesity and gut microbiota metabolites, such as short-chain fatty acids, medium-chain fatty acids, amino acids, amines, and bile acids, are also summarized. Targeting gut microbiota and metabolites might be a promising strategy for interventions aimed at reducing pediatric overweight/obesity.